URBAN TERABITHIA, RUANG RETREAT KAWASAN TAMBORA - Edrik Tasbun; Agustinus Sutanto (Jurusan Arsitektur dan Perencanaan, 2020)
Tambora District, which is the most densely populated region in Southeast Asia, is one of the informal sectors in the city of Jakarta. The development of an increasingly capitalist city, so that there are imbalances in the formal and informal sectors, causing social, mental, and other problems. Tambora Retreat Spaces with the Urban Accupunchture architecture approach becomes a forum by creating a new environmental reality for the informal sector to help them strengthen their role in the inner city. This project presents Urban zen garden and biophilic design as a passive media retreat and technology retreat for active media retreats. This place also plays a role in replacing the role of open space and third-places facilities for those who are lost are replaced by residential settlements that are increasingly congested every year. The project also focuses on creating a media for community growth space of all ages and social status in community life, based on the Ville Spatiale concept of Yona Friedman to become a forum for interaction, rehabilitation, and inspirationKeywords: Growth Spaces; Nature; Rehabilitation; Technology AbstrakKecamatan Tambora yang menjadi kawasan dengan tingkat penduduk paling padat se-Asia Tenggara ini, merupakan salah satu area yang didominasi permukiman informal di kota Jakarta. Perkembangan kota yang semakin kapitalis membuat adanya ketimpangan pada sektor formal dan informal, sehingga menimbulkan permasalahan sosial, mental, dan lainnya. Tambora Retreat Spaces dengan pendekatan arsitektur Urban Accupuncture menjadi wadah dengan menciptakan sebuah realita lingkungan baru bagi informalitas untuk membantu mereka memperkuat perannya pada bagian di dalam kota. Proyek ini menghadirkan Urban zen garden dan biophilic design sebagai media retreat pasif dan technology retreatment untuk media retreat aktif. Tempat ini juga berperan dalam menggantikan peran ruang terbuka serta fasilitas ruang ketiga bagi mereka yang hilang digantikan oleh permukiman warga yang semakin padat setiap tahunnya. Proyek ini juga berfokus untuk menciptakan sebuah media ruang tumbuh masyarakat dari segala umur dan status sosialnya dalam kehidupan masyarakat, dengan berlandaskan konsep Ville Spatiale dari Yona Friedman untuk menjadi wadah interaksi, rehabilitasi, dan terinspirasi.